Sistem Pakar Deteksi Penyakit Ikan Lohan Menggunakan Metode Forward Chaining - Richard Alexander; Djoni Haryadi Setiabudi; Alexander Setiawan (Universitas Kristen Petra, 2022)
Flowerhorn care has different handling, where this can affects how to cultivate and how to treat it. Where if the treatment given is not good, the quality of the fish produced also decreases, which can greatly affect the selling price of the fish.The problem that the author want to solve is by utilizing an android application that functions to diagnose diseases that exist in flowerhorn by using an expert system based on the Forward Chaining Method to diagnose the symptoms that arise in flowerhorn fish.The test was carried out on a collection of interview data in the form of disease symptoms and the application made was able to diagnose flowerhorn with the results of the method test being able to achieve an accuracy value of 80%.